Laparoscopic Nissen Fundoplication Outcomes in Children with Gastroesophageal Reflux Disease and Hiatus Hernia: Retrospective Trial - Shawkat Mohamad, Abdelhalem; Ali Ibrahim, Ibrahim; Ahmed Mohamed Nagaty, Mohamed; Yassen Fathy, Khalaf; Taher, Heba; M Akoula, Ahmed (Journal of Neonatal Surgery, 2025)
Background Diagnosis and treatment of infant gastroesophageal reflux (GER) can be accomplished in a number of ways. Although the long-term effects on high-risk infants are unknown, laparoscopic surgery has led to an increase in the number of children needing antireflux surgery. This study aims to assess the outcome of laparoscopic nissen fundoplication in children younger than 18 years old. Methods Retrospective study of infants younger than 18 years' old who underwent laparoscopic Nissen fundoplication (Lap-NF) between 2020 and 2023 had their outcomes tracked until 2024. Results There were 44 cases, with a mean weight of 12.9 kg±3.5 and a median age of 3.32 year±1.9. An improved respiratory status following nasoduodenal feeding tube insertion was a typical rationale for surgical consultation.There were minimum postoperative problems. Median times for feeds were 1.61±0.72 days and for reaching the objective were 3.93±1.8 days. Hospital stay range from 3 : 7 days . During the postoperative phase, Three patient required readmission due to recurrence. Conclusion In children younger than 18 years old, Nissen fundoplication is a successful treatment for GER symptoms and hiatus hernia (HH). In this population, the procedure has a low rate of complications.